Preliminary studies of the time-dependent shear and uniaxial tensile behaviour of oriented polymers - Clayton, D. (College of Aeronautics, 1969)
Summary The work reported in this memo is the initial stages of an investigation of the time-dependent behaviour of certain anisotropic polymers. In the first instance low density polyethylene with a transversely isotropic symmetry is being examined. Different degrees of anisotropy have been induced by cold drawing and the time dependent material parameters necessary to describe the stiffness of the anisotropic polyethylene have been determined. This involved the measurement of uniaxial tensile creep: lateral contraction creep, and torsional creep under conditions of constant load at 20°C ± 0.5°C. The tensile creep and contraction creep apparatus has been described elsewhere (Darlington (a) 1968) and only the principle of the apparatus is discussed here. The torsional creep apparatus is described in detail. Analysis of the experimental data is not yet complete. The data is tabulated in section 5 and a preliminary analysis is presented in section G. Details of proposed future work are discussed in section 7.